(untitled) (Journal of history, 2020)
The article describes the specific results of the study shezhire of Kazakhs, investigated by the author as a genealogical memory and historical source, as a cultural tradition and original forms of historical knowledge of the Kazakh people.In this article, shezhire represented as a set of historical and genealogical materials,which was used to study the law, tribal life and ethnic composition of the population of the steppe.The concept of «shezhire» means «family tree», «memory», «genealogy».In this article, the author describes a shezhire how the document, containing the most diverse historical information,which includes, primarily, folk genealogy. Key words: shezhire, genealogy, genus, tribe.